Answer:
the answer has to be 3(17-y)
Step-by-step explanation:
I'm pretty sure about that cause what I did at first is subtract the numbers.
<em>6</em><em>0</em><em>-3y-9</em>
=51-3y
factor our 3 from the expression.
3(17-y)
Answer:
9 students
Step-by-step explanation:
3/4 students like pbj sandwiches
4 * 3 = 12
3 * 3= 9
9/12
9 students like pbj sandwiches
Answer:y+7x=8
Step-by-step explanation:y=-7x+8
7x needs to be on the variable side
y+7x=8
Answer:
c (0,-4)
Step-by-step explanation:
-5x+y = -4
4x - 4y =16
Solve the first equation for y since we are using substitution.
-5x+y = -4
Add 5x to each side
-5x+5x+y = -4+5x
y = 5x-4
Substitute this equation y = 5x-4 into the second equation.
4x -4(5x-4) = 16
Distribute the -4
4x - 4(5x) -4(-4) = 16
4x-20x +16 = 16
Combine like terms
-16x +16 =16
Subtract 16 from each side
-16x+16-16 = 16-16
-16x =0
Divide by -16
x=0
But we still need to find y
y = 5x-4
y = 5(0) -4
y = -4